The Role of Parents and Schools Behind the Riding Policy for Primary School Students - Pangestu, Sevirgo Akbar Putra; Abduh, Muhammad (International Conference on Education for All, 2024)
The current state of traffic conditions in Indonesia is quite worrying; many violations occur, both intentionally and unintentionally. Many minors ride motorcycles without knowing the traffic rules. This research focuses on problems related to school regulations that allow students to ride motorbikes to school, as well as the role of parents regarding the use of motorbikes for underage children. This research uses a qualitative approach with a case study research method. Data collection techniques were carried out through observation, followed by interviews and documentation. The results of the research show that there are factors regarding permission from parents and family, including: 1) the role of parents because they are busy and cannot take their children to school; 2) the efficiency of time used because of the long distance from home to school and the absence of public transportation in the area; 3) a lack of parental guidance regarding understanding traffic; 4) invitations from peers. 2) Allowing them to ride motorbikes has an influence on their behavior patterns, including making them more skilled at riding motorbikes. Because in that area, when they enter junior high school (SMP), because the distance from home is increasingly far away, their parents allow them to ride motorbikes to school. 3) Parents have a very important role in supervising children. The family is considered a basic ecology in which a childs behavior is manifested from childhood in a negative or positive way.